Influence of borination, boron cementation of steel 45 and viscosity of a lubricant on the parameters of adhesion bond in the steel 45 - 40x system - Kubich, V.I.; Cherneta, O.G.; Yurov, V.M. (Eurasian Physical Technical Journal, 2021)
In the work, the regularities of changes in the shear strength of the adhesive bond τ and the piezoelectric coefficient β in the metal systems "steel 45 - 40X", "steel 45+В-40Х", "steel 45+ВС-40Х" were obtained during physical modeling of the materials I-20A, Wolf 10W-40, TAD-17i, Litol-24 with distinctive dynamic viscosities using the additional equipment of the SMTs-2 friction machine. It has been established that a twofold increase in the shear rate causes a decrease in the piezoelectric coefficient in the "steel 45+VS - 40X" system by a factor of 1.2-1.6 for Wolf 10W-40, TAD-17i, Litol-24 lubricants and its relative similarity independent of dynamic viscosity. At the same time, a twofold increase in the shear rate in the "steel 45+B-40X" system also causes a decrease in the piezoelectric coefficient by a factor of 1.16-1.38 for all tested lubricants and its alignments, as in the "steel 45+VS" system, does not observed. It was found that the clearly expressed regularity of the effect of the equivalent dynamic viscosity on the strength of the adhesive bond at p = 0 MPa is not revealed, and the nature of the manifestation is predetermined by a possible change in the mechanism of intermolecular interaction, which depends on the structure of the molecules of lubricants. It was determined that the piezoelectric coefficient naturally decreases with an increase in dynamic viscosity in the entire considered range of normal pressures.
Keywords: metal system; tangential strength; shear rate; piezoelectric coefficient; pressure; dynamic viscosity